Cyclic vomiting syndrome is a prevalent and under‐recognized condition in the gastroenterology outpatient clinic. Issue 1 (26th July 2017) - Sagar, R. C.; Sood, R.; Gracie, D. J.; Gold, M. J.; To, N.; Law, G. R.; Ford, A. C.
Abstract: Background: Cyclic vomiting syndrome (CVS) is a functional gastrointestinal disorder (FGID) characterized by intermittent episodes of nausea and vomiting. Our aim was to report its prevalence and associated features. Methods: Data concerning demographics, symptoms, and psychiatric comorbidity were collected. Symptoms compatible with CVS were classified as per Rome III criteria. We recorded whether a diagnosis of CVS was considered in patients after negative investigation. We compared demographics and association with other FGIDs in patients with and without CVS. Key Results: 920 of 1002 patients provided data. Of the 920 patients, 112 (12.2%) had symptoms compatible with CVS. Thirteen (11.6%) of these had an organic cause for their symptoms, but 99 patients (88.4%) were deemed to have CVS (prevalence=10.8%). Organic causes for symptoms compatible with CVS included gastroparesis, large hiatus hernia, achalasia, and small bowel obstruction. Only 39.4% of patients with CVS were asked about vomiting symptoms at their initial consultation, and a diagnosis of CVS was considered in only four (4.0%) of the 99 patients. CVS was associated with younger age, tobacco smoking, never having married, psychiatric comorbidity, and presence of symptoms compatible with other FGIDs ( P ≤.01). Conclusions and Inferences: Prevalence of CVS in this outpatient gastroenterology adult population was 10.8%. Identified associations included younger age, tobacco smoking, psychiatric comorbidity, and symptoms compatible with other FGIDs. The condition was considered as a possible diagnosis in <5% of patients who met the diagnostic criteria. Abstract : Cyclic vomiting syndrome is a functional gastrointestinal disorder that is poorly understood in adults. Our study suggests a prevalence in adults of 7% but the diagnosis was only considered in a minority. Education of physicians may improve diagnostic delay, reduce financial burden, and enable appropriate management.